Europe and Iran’s Nuclear Crisis - Alcaro, Riccardo. author. aut Link
XI, 293 p. 2 illus.
Keywords: This book investigates the European involvement in managing the nuclear dispute with Iran, shedding new light on EU foreign policy-making. The author focuses on the peculiar format through which the EU managed Iran’s nuclear issue: a ‘lead group’ consisting of France, Germany and the UK and the High Representative for EU foreign policy (E3/EU). The experience of the E3/EU lends credibility to the claim that lead groups give EU foreign policy direction and substance. The E3/EU set up a negotiating framework that worked as a de-escalating tool, a catalyst for Security Council unity and a forum for crisis management. They inflicted pain on Iran by adopting a comprehensive sanctions regime, but did so only having secured US commitment to a diplomatic solution. Once the deal was reached, they defended it vigorously. The E3/EU may have been supporting actors, but their achievements were real. .